Ubiquitin signalling: controlling the message of surface immune receptors. Issue 1 (2nd May 2021) - Trujillo, Marco
Summary: Microbial attack is first detected by immune receptors located at the plasma membrane. Their activation triggers a plethora of signalling cascades that culminate in the immune response. Ubiquitin and ubiquitin‐like protein modifiers play key roles in controlling signalling amplitude and intensity, as well as in buffering proteome imbalances caused by pathogen attack. Here I highlight some of the important advances in the field, which are starting to reveal an intertwined and complex signalling circuitry, which regulates cellular dynamics and protein degradation to maintain homeostasis.